Petalidium engoense (Acanthaceae), a new species from Angola and Namibia, with notes on phenotypic plasticity in the genus - Swanepoel, Wessel; Becker, Rolf W.; Wyk, Abraham E. Van (Phytotaxa, 2025)
Petalidium engoense, first collected in May 2025, is here described as a new species. It is a range-restricted species, only known from the western edge of the escarpment zone (Great Escarpment of southern Africa), in the hilly area bordering the Engo Valley (northwestern Namibia), and to the north of Espinheira (southwestern Angola), in the Kaokoveld Centre of Endemism. It grows amongst boulders on arid hillsides, and along an ephemeral riverbed. Diagnostic characters for P. engoense include the pale greyish green appearance of the plants, ashy-grey to white fissured bark on older stems, vegetative parts with a dense white indumentum of very small stellate (stellulate) and dendritic trichomes appearing tomentose, semi-succulent leaves, burgundy flowers borne in short few-flowered dichasia with inflorescence axis becoming spiny with age, and narrowly ovate, attenuate to acute, prominently reticulate bracteoles. The flowers of P. engoense are distinctive in having all lobes coloured burgundy, and the anterior lobe with two yellow ensiform nectar guides. A comparison of key morphological features distinguishing P. engoense from P. namibense, its closest relative in appearance, is provided. Based on IUCN Red List criteria, a provisional conservation assessment of Critically Endangered (CR) is recommended for the new species. The paper also summarises current knowledge of phenotypic plasticity within Petalidium in response to environmental variation. This contribution forms part of ongoing taxonomic studies on the genus.